Secondary Outcomes From the Child/Adolescent Anxiety Multimodal Study: Implications for Clinical Practice - Albano, Anne Marie (Evid Based Pract Child Adolesc Ment Health, 2017)
BACKGROUND: Controlled evaluations comparing medication, cognitive-behavioral therapy (CBT), and their combination in the treatment of youth anxiety have predominantly focused on global ratings by independent evaluators. Such ratings are resource-intensive, may be of limited generalizability, and do not directly inform our understanding of treatment responses from the perspective of treated families. We examined outcomes from the perspective of treated youth and parents in the Child/Adolescent Anxiety Multimodal Study (CAMS). METHODS: Participants (N=488; ages 7–17 years) who had a primary diagnosis of separation, social, and/or generalized anxiety disorder were randomly assigned to a treatment condition in the CAMS trial. Linear mixed-effects and ANCOVA models examined parent- and youth-reported anxiety symptoms, impact of anxiety, broader internalizing and externalizing psychopathology, depressive symptoms, and family burden throughout the 12-week acute treatment phase and 6-month follow-up. RESULTS: At week 12, combination treatment showed superiority over placebo, sertraline, and CBT with regard to parent-reported youth anxiety symptoms, and sertraline and CBT as monotherapies showed superiority over placebo with regard to parent-reported youth anxiety. Combination therapy and sertraline also showed week 12 superiority over placebo with regard to parent-reported internalizing psychopathology, and superiority over placebo and CBT with regard to parent-reported impact of anxiety, family burden, and youth depressive symptoms. By week 36, parent reports of many youth outcomes were comparable across active conditions. Youth measures tracked parent measures on many outcomes. CONCLUSIONS: Findings were drawn on brief, readily available questionnaires that in conjunction with clinician measures can inform patient-centered care and collaborative decision-making. Trial Registry Name: Child and Adolescent Anxiety Disorders (CAMS) Registry identification number: NCT00052078 Registry URL: https://www.clinicaltrials.gov/ct2/show/NCT00052078